Desempenho zootécnico e imunoparâmetros do camarão litopenaeus vannamei alimentados com ração suplementada com spirulina platensis em sistema de recirculação - Pereira, Nayagra Vidal (2015)
In shrimp farming, food has a major effect on growth, survival of individuals and total cost of production, and the quality of water, depending on the adopted food strategy. Although the Litopenaeus vannamei shrimp has a well developed technological package, the high cost of feed consists of an obstacle in its development. In addition, diseases, inadequate management and environmental impacts cause serious problems in production. Thus, the present study was performed in order to evaluate the performance and immune parameters of juvenile shrimp L. vannamei fed a balanced commercial diet for fish, with 28 % crude protein, supplemented with 26 % Spirulina platensis flour (treatment) as well as the removal of nitrogen compounds by the microalga in a recirculation system. The control was used balanced commercial feed for shrimp, with 40 % crude protein. The survivals of 53 and 63 %, for the treatment and control, respectively, may have been influenced by low oxygen concentration 2.01 ± 0.5 mg/L 18h observed even with the use of mechanical aeration. Statistically, the final weight of the treatment was lower than in the control group, however, the values obtained are similar or larger by values found in the scientific literature. Despite the gain in value and average daily weight of the present treatment is statistically lower than the control, the values of 12,92 ± 0,14 g e 0,25 ± 0,01 g.dia-1, respectively, were higher than in the referenced literature. Analyzing the imunoparâmetros there was a statistically significant difference in the variables: total count of hemocytes (CTH), total protein concentration (CP) and activity fenoloxidade (PO). CTH and CP were 7 and 53 % greater in treatment than in the control, showing that the use of diet supplemented with S. platensis may be capable of increasing the immunocompetence of the animal. There was no statistical difference between hyaline hemocytes (HH) and granular (HG) between control and treatment due to lack of exposure to a biological challenge in vivo.